Effect of air layer thickness on melting kinetics and heat transfer in horizontally oriented hemispherical phase change material enclosures - Abbas Fadhil Khalaf; Farhan Lafta Rashid; Mudhar A. Al-Obaidi; Hayder I. Mohammed; Arman Ameen; Ephraim Bonah Agyekum (International Journal of Thermofluids)
Phase change materials (PCMs) in thermal energy storage systems often encounter unintended air gaps that critically affect performance, yet their effects in hemispherical enclosures remain unexplored. This research delves into the critical role of air layer thickness in modulating the melting kinetics and heat transfer performance of PCM within horizontally oriented hemispherical enclosures—a configuration with considerable applications for thermal energy storage (TES) systems. This research has systematically quantified how air layer thickness (0–3 mm) affects PCM melting dynamics using advanced ANSYS/FLUENT 16 simulations. The absence of an air layer (0 mm) affords the fastest melting, driven by unobstructed natural convection and conduction. In other hand, incremental air layer thicknesses (1 mm, 2 mm, 3 mm) have introduced enlightened thermal resistance, delaying melting completion by 15 %, 30 %, and 45 %, respectively. In this regard, a 3 mm air layer has exhibited the most noticeable insulating effect, overwhelming the convective flow velocities by 35–40 % and creating non-uniform temperature distributions of 18–22 °C gradients. The obtained results disclose an essential trade-off. This is specifically disclosed as while air layers can enhance insulation, they obstruct heat transfer competence, extending the melting duration from 85 min (0 mm) to 123 min (3 mm). This research delivers actionable visions for optimising air gap design in PCM-based systems, balancing thermal regulation requirements with energy storage performance. The associated results are predominantly relevant for applications necessitating detailed thermal management, such as building-integrated TES and electronic cooling, where hemispherical enclosures offer geometric advantages.